Determination of the naturally occurring vanadium-complex amavadin in Amanita muscaria with HPLC-ICPMS. Issue 5 (8th April 2021) - Braeuer, Simone; Walenta, Martin; Steiner, Lorenz; Goessler, Walter
Abstract : The determination of the two isomers of amavadin and other V species in Amanita muscaria with HPLC-ICPMS. Abstract : Amanita muscaria, also known as the fly agaric mushroom, can accumulate vanadium (V), with up to several hundred mg V kg −1 dry mass. It is long known that V is present in A. muscaria as a complex called amavadin, but methods for the investigation of the distribution and biosynthesis of amavadin in mushrooms are missing. Here, we describe the development of the first sensitive method for the determination of amavadin and other V-containing compounds in environmental samples by employing high performance liquid chromatography (HPLC) and inductively coupled plasma mass spectrometry (ICPMS). A strong anion-exchange column serves as the stationary phase, and the mobile phase consists of an aqueous ammonium citrate buffer and ethylenediaminetetraacetate (EDTA). The concentration and pH of the mobile phase as well as the column temperature were evaluated to optimize the separation. With the final method, amavadin is eluted in less than 17 minutes, and its limit of detection is 0.05 μg V L −1 . Moreover, the compound's two isomers are separated from each other and can be quantified independently. The method was applied to extracts of fruit-body samples of A. muscaria . The extraction efficiency was 74 ± 12%, and amavadin accounted for 75–96% of the extracted V. In addition, significant concentrations of other V species could be detected, which have never been described before. Our results demonstrate that V speciation in mushrooms is more complex than assumed until now and that more in-depth investigations on this matter are needed. The developed method enables the investigation of organic and inorganic V species in the environment, even at low concentrations.